Copper cobaltate composite cobalt molybdate nano material, preparation method thereof, negative plate and battery
The preparation of copper cobalt acid composite cobalt molybdate nanomaterials through solvothermal reactions solves the problem of insufficient conductivity and lithium ion migration power of copper cobalt acid in lithium-ion batteries, and achieves high specific capacity and good rate performance of the material.
Patent Information
- Application Number
- CN202411571315.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
Existing cobalt copper materials have problems with low intrinsic electron conductivity and low lithium ion mobility in lithium-ion batteries.
Prepare copper cobaltate composite cobalt molybdate nanomaterial by solvothermal reaction. The specific steps include dissolving the copper source, cobalt source and molybdenum source in different solvents, stirring and sonication, and then performing solvent-thermal reaction and calcination to obtain CuCo2O4 @CoMoO4 nanomaterial.
The electrochemical performance and cyclic stability of cobalt molybdate nanomaterials have been improved, and the specific capacity and rate performance of lithium-ion batteries have been significantly improved.
Smart Images

Figure CN119430303A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a copper cobaltate composite cobalt molybdate nanomaterial and a preparation method thereof, a negative electrode sheet, and a battery. Background Art
[0002] With the growing demand for high energy density storage in portable electronic devices, power tools and electric vehicles, the development of high-performance and high-specific-energy lithium-ion batteries is of vital importance. However, due to the limited specific capacity (372 mAh g -1 ), the specific energy of conventional lithium-ion batteries is not sufficient for these applications.
[0003] Lithium-ion batteries have been widely used in power and energy storage systems due to their low cost, long life, and environmental friendliness. The capacity and rate performance of lithium-ion batteries mainly depend on the electrochemical properties of the anode and cathode materials. However, commercial graphite anode materials are limited by 372 mAhg -1 The low theoretical capacity, poor rate capability and potential safety issues of spinel TMOs are the limitations of TMOs. Therefore, binary and ternary spinel TMOs, especially cobalt-containing spinel TMOs, are promising materials to replace graphite anodes due to their high theoretical capacity and optimal composition and morphology. Due to the high cost and toxicity of cobalt, it is highly desirable to partially replace cobalt with relatively cheap and environmentally friendly metals and explore their lithium recyclability. CuCo2O4 is electrochemically active in lithium-ion battery anodes and has been applied to lithium-ion batteries and has shown an impressive performance of 874 mAh g -1 However, pure CuCo2O4 undergoes severe volume expansion, aggregation, and crystal structure pulverization during lithiation / delithiation, and also has low intrinsic electronic conductivity and low lithium ion migration kinetics.
[0004] With the growing demand for high energy density storage in portable electronic devices, power tools and electric vehicles, the development of high-performance and high-specific-energy lithium-ion batteries is of vital importance. However, due to the limited specific capacity (372 mAh g -1 ), the specific energy of conventional lithium-ion batteries is not sufficient for these applications.
[0005] Therefore, exploring new electrode materials with higher capacity is one of the most important research directions for LIBs. Transition metal oxides (TMOs), especially cobalt-based oxides with spinel structure, have been widely studied as possible substitutes for carbonaceous anode materials due to their higher theoretical capacity. Considering the high cost of Co, ternary cobalt oxides that partially replace Co with cheaper metals such as Ni, Zn, Fe, Mg, Cu, Mn, etc. are more practical negative electrode materials.
[0006] Chowdari's team successfully introduced copper to partially replace cobalt to obtain CuCo2O4 nanoparticles (Sharma, Yogesh, et al. 2007) providing 745 mAhg -1 Capacity (at 60mA g -1 After 20 cycles at a current rate of 100 mAh g -1 Reddy et al. also reported a method for synthesizing CuCo2O4 nanoparticles using a molten salt method (MV Reddy, Yet al. 2012), which showed a discharge capacity of ~740 mAh g after 40 cycles. -1 Sun et al. used porous silica as a template (Sun, S., et al. 2013) to obtain a mesoporous CuCo2O4 structure at about 1000 mAg -1 The capacity is about 250 mAh g -1 After 6 cycles, the discharge capacity remains at 900 mAhg -1 Although the high capacities reported in these early works clearly indicate that CuCo2O4 has good potential for LIB applications, the material tends to collapse during battery testing, so several issues must be addressed. For example, all reports on CuCo2O4 anodes to date have used relatively low current densities (e.g., less than 100 mA g -1 and limited number of cycles (<50) for LIB characterization. In addition, the rate performance of the CuCo2O4 anode needs to be further optimized, as the current density increases to about 800 mA g -1 When the capacity is 250mAhg -1 Following the sharp decline, it is clear that operational stability and high-rated performance are two key issues that need to be improved before the widespread application of CuCo2O4 can be achieved. Summary of the invention
[0007] In view of this, the embodiments of the present application provide a copper cobaltate composite cobalt molybdate nanomaterial and a preparation method thereof, a negative electrode sheet and a battery, which can effectively overcome the defects of copper cobaltate in the prior art, that is, low intrinsic electronic conductivity and low lithium ion migration power.
[0008] A first aspect of the present application provides a method for preparing a copper cobaltate composite cobalt molybdate nanomaterial, comprising the following steps:
[0009] Step 1, weighing a copper source and a cobalt source, dissolving them in a first solvent, stirring evenly, to obtain a solution A; weighing a molybdenum source and a cobalt source, dissolving them in a second solvent, stirring evenly, to obtain a solution B; mixing solution A and solution B to obtain a mixed solution;
[0010] Step 2, subjecting the mixed solution to a solvothermal reaction to obtain a precipitate, and washing and drying the precipitate to obtain an intermediate substance;
[0011] Step 3: calcining the intermediate material to obtain a copper cobaltate composite cobalt molybdate nanomaterial. The chemical formula of the copper cobaltate composite cobalt molybdate nanomaterial is: CuCo2O4@CoMoO4.
[0012] In some embodiments that may include the above embodiments, step one specifically includes the following steps:
[0013] A copper source and a cobalt source are weighed and dissolved in an organic solvent, and then urea is added, and the mixture is stirred and mixed evenly under a magnetic stirrer to obtain a solution A; a molybdenum source and a cobalt source are weighed and dissolved in dilute nitric acid, and the mixture is stirred and mixed evenly under a magnetic stirrer to obtain a solution B; then solution B is slowly poured into solution A, and stirring is continued and ultrasonic treatment is performed to obtain a mixed solution.
[0014] Preferably, 13.33 mmol of urea is added and dissolved in 5 ml of dilute nitric acid; solution B is slowly poured into solution A and stirring is continued at a speed of 200 rpm.
[0015] It should be noted that step one may also include the following steps: weighing a copper source, a cobalt source and urea, dissolving them in an organic solvent, stirring evenly to obtain solution A; weighing a molybdenum source and a cobalt source, dissolving them in dilute nitric acid, stirring evenly to obtain solution B; mixing solution A and solution B to obtain a mixed solution.
[0016] In some embodiments that may include the above embodiments, in step 2, the temperature of the solvothermal reaction is 140° C., and the time of the solvothermal reaction is 10 h.
[0017] In some embodiments that may include the above embodiments, in step three, the calcination conditions are: calcination is carried out in air, the calcination temperature is 550° C., and the calcination time is 1-5 hours.
[0018] In some embodiments that may include the above embodiments, in step 1, the molar ratio of copper atoms, cobalt atoms, and molybdenum atoms in the copper source, cobalt source, and molybdenum source is 2:(4.5-5.5):(0.5-1.5).
[0019] In some embodiments that may include the above embodiments, in step one, the copper source is one or more of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, and copper chloride; the cobalt source is one or more of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt chloride, and cobalt tetroxide; the molybdenum source is one or more of ammonium molybdate, sodium molybdate, and magnesium molybdate.
[0020] In some embodiments that may include the above embodiments, the organic solvent is one or more of N,N-dimethylformamide, ethanol, and acetone;
[0021] The second aspect of the embodiment of the present application further provides a copper cobaltate composite cobalt molybdate nanomaterial, which is prepared by the copper cobaltate composite cobalt molybdate nanomaterial using the above method.
[0022] The third aspect of the embodiment of the present application further provides a negative electrode sheet, which contains the copper cobaltate composite cobalt molybdate nanomaterial mentioned above or the copper cobaltate composite cobalt molybdate nanomaterial prepared by the above method.
[0023] The fourth aspect of the embodiment of the present application further provides a battery, comprising the above-mentioned negative electrode sheet, and also comprising a battery casing, a positive electrode sheet, a separator and an electrolyte.
[0024] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0025] 1. This application is an in-situ metal oxide composite material, which can improve the ionic conductivity of copper cobalt oxide composite cobalt molybdate nanomaterials as lithium ion battery electrode materials by using a solvent thermal method;
[0026] 2. The present application prepares copper cobaltate composite cobalt molybdate nanomaterials by a solvent thermal method. The preparation method has a simple process, is easy to implement, has high repeatability, can reduce energy consumption, has a high raw material utilization rate, and can prepare copper cobaltate composite cobalt molybdate nanomaterials with excellent crystallinity and electrochemical properties and high purity. The material exhibits excellent electrochemical properties and extremely good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 This is the XRD diagram of the CuCo2O4 nanomaterial in Example 2 of the present application;
[0029] Figure 2This is the XRD pattern of the CuCo2O4@CoMoO4-(1:1) nanomaterial in Example 2 of the present application;
[0030] Figure 3 This is a rate performance diagram of the CuCo2O4 of comparative example 1 and the CuCo2O4@CoMoO4-(1:1) nanomaterial of example 2 of the present application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] In order to solve the technical problems of low intrinsic electronic conductivity and low lithium ion migration power in copper cobalt oxide as negative electrode material in the prior art, the embodiment of the present application prepared a material with excellent electrochemical properties, which showed excellent electrochemical properties and excellent cycle stability in electrochemical tests.
[0033] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0034] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0035] Example 1
[0036] 2mmol of copper nitrate trihydrate, 4mmol of cobalt nitrate hexahydrate, and 13.33mmol of urea were placed in 60ml of N,N-dimethylformamide, and stirred under magnetic stirring for 0.5h, which was recorded as solution A; 1mmol of ammonium molybdate and 1mmol of cobalt nitrate hexahydrate were dissolved in 5ml of dilute nitric acid solution, and stirred, which was recorded as solution B; then solution B was slowly poured into solution A to make the substances therein fully dissolved in the solvent, to obtain a mixed solution;
[0037] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The obtained precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate substance powder;
[0038] The intermediate substance powder obtained was placed in a muffle furnace at 550°C in air and sintered for 3 hours with a heating rate of 5°C / min. After cooling, copper cobaltate composite cobalt molybdate nanomaterials were obtained, abbreviated as CuCo2O4@CoMoO4-(1-0.5) material.
[0039] Example 2
[0040] 2mmol of copper nitrate trihydrate, 4mmol of cobalt nitrate hexahydrate and 13.33mmol of urea were placed in 60ml of N,N-dimethylformamide and stirred under magnetic stirring for 0.5h, which was recorded as solution A; 2mmol of ammonium molybdate and 2mmol of cobalt nitrate hexahydrate were dissolved in 5ml of dilute nitric acid solution and stirred, which was recorded as solution B; then solution B was slowly poured into solution A to make the substances therein fully dissolved in the solvent, to obtain a mixed solution;
[0041] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The obtained precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate substance powder;
[0042] The obtained intermediate substance powder was placed in a muffle furnace at 550°C in air and sintered for 3 hours with a heating rate of 5°C / min. After cooling, copper cobaltate composite cobalt molybdate nanomaterials were obtained, abbreviated as CuCo2O4@CoMoO4-(1:1) material.
[0043] Example 3
[0044] 2mmol of copper nitrate trihydrate, 4mmol of cobalt nitrate hexahydrate and 13.33mmol of urea were placed in 60ml of N,N-dimethylformamide and stirred under magnetic stirring for 0.5h to be recorded as solution A; 3mmol of ammonium molybdate and 3mmol of cobalt nitrate hexahydrate were dissolved in 5ml of dilute nitric acid solution and stirred to be recorded as solution B; then solution B was slowly poured into solution A to make the substances therein fully dissolved in the solvent to obtain a mixed solution;
[0045] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The obtained precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate substance powder;
[0046] The obtained intermediate material powder was placed in a muffle furnace at 550°C in air and sintered for 3 hours with a heating rate of 5°C / min. After cooling, copper cobaltate composite cobalt molybdate nanomaterials were obtained, abbreviated as CuCo2O4@CoMoO4-(1:1.5) material.
[0047] Example 4
[0048] 2mmol of copper nitrate trihydrate, 4mmol of cobalt nitrate hexahydrate and 13.33mmol of urea were placed in 60ml of N,N-dimethylformamide and stirred under magnetic stirring for 0.5h, which was recorded as solution A; 2mmol of ammonium molybdate and 2mmol of cobalt nitrate hexahydrate were dissolved in 5ml of dilute nitric acid solution and stirred, which was recorded as solution B; then solution B was slowly poured into solution A to make the substances therein fully dissolved in the solvent, to obtain a mixed solution;
[0049] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The obtained precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate substance powder;
[0050] The obtained intermediate material powder was placed in a muffle furnace at 550°C in air and sintered for 3 hours. The heating rate was set to 5°C / min. After cooling, copper cobaltate composite cobalt molybdate nanomaterials were obtained, abbreviated as CuCo2O4@CoMoO4-1-1h material.
[0051] Example 5
[0052] 2mmol of copper nitrate trihydrate, 4mmol of cobalt nitrate hexahydrate, and 13.33mmol of urea were placed in 60ml of N,N-dimethylformamide, and stirred under magnetic stirring for 0.5h, which was recorded as solution A; 2mmol of ammonium molybdate and 2mmol of cobalt nitrate hexahydrate were dissolved in 5ml of dilute nitric acid solution, and stirred, which was recorded as solution B; then solution B was slowly poured into solution A to make the substances therein fully dissolved in the solvent, to obtain a mixed solution;
[0053] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The obtained precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate substance powder;
[0054] The obtained intermediate material powder was placed in a muffle furnace at 550°C in air and sintered for 3 hours with a heating rate of 5°C / min. After cooling, copper cobaltate composite cobalt molybdate nanomaterials were obtained, abbreviated as CuCo2O4@CoMoO4-1-5h material.
[0055] Comparative Example 1
[0056] 2 mmol of copper nitrate trihydrate, 4 mmol of cobalt nitrate hexahydrate, and 13.33 mmol of urea were placed in 60 ml of N,N-dimethylformamide, stirred for 0.5 h under magnetic stirring, and ultrasonicated for 3 minutes to fully dissolve the substances in the solvent to obtain a mixed solution;
[0057] The mixed solution was then placed in a reactor for high temperature and high pressure reaction, and the reactor was placed in a blast drying oven, the temperature was set to 140°C, and the reaction time was 10 hours. The precipitate was then washed three times with N,N-dimethylformamide, and placed in a blast drying oven again for 20 hours at 80°C to obtain an intermediate powder.
[0058] The obtained intermediate powder was placed in a muffle furnace at 550°C in air and sintered for 3 hours with a heating rate of 5°C / min. After cooling, copper cobalt oxide material was obtained, abbreviated as CuCo2O4 pure sample.
[0059] Application Examples
[0060] The CuCo2O4@CoMoO4-(1:1) material prepared in Example 2 is used as an electrode material in a lithium-ion battery, specifically comprising the following steps:
[0061] (1) Preparation of negative electrode: 70 mg of each of the materials prepared in Comparative Example 1 and Example 2 were weighed, mixed with 20 mg of conductive agent superP and 10 mg of binder polyvinylidene fluoride (PVDF) and ground for 20 min to obtain a uniformly mixed negative electrode material, 0.5 mL of N-methylpyrrolidone was added, and grinding was continued to obtain a uniformly dispersed negative electrode material, and the negative electrode material was evenly coated on a copper foil with a scraper, and vacuum dried at 80° C. for 12 h to obtain a negative electrode sheet;
[0062] (2) Assembling button cells: Select lithium metal as the positive electrode material. In a glove box filled with argon, cut the lithium metal foil into round pieces with a diameter of 16 mm. Place the cut lithium metal pieces in the positive electrode shell of the 2016 button cell and fix them with gentle pressure. Assemble the battery. Place the diaphragm, negative electrode sheet and electrolyte in the positive electrode shell in turn. Cover the negative electrode shell and press it with a special tool to ensure a good seal. The diaphragm is Celgard2400 and the electrolyte is LiPF6 / EC:DEC with a concentration of 1M (volume ratio 1:1).
[0063] The prepared 2016-type button battery was tested on the Blue Electric test system. The electrochemical energy storage performance of the prepared lithium-ion battery was tested. Figure 3 This is the cycle performance diagram of CuCo2O4 and CuCo2O4@CoMoO4-(1:1) materials at different charge and discharge current densities of 0.2A / mg, 0.3A / mg, 0.5A / mg, 1A / mg, and 2A / mg.
[0064] Depend on Figure 3 It can be seen that the CuCo2O4 and CuCo2O4@CoMoO4-(1:1) prepared in Comparative Example 1 and Example 2 respectively are assembled into a half-cell (with lithium sheet as the counter electrode), and the specific capacity is about 1065mAh / g and 1227mAh / g at a current of 0.2A / mg; the half-cell assembled by CuCo2O4@CoMoO4-(1:1) in Example 2 has good charge and discharge stability, and the lithium-ion battery is also very stable.
[0065] Depend on Figure 3 It can be seen that the CuCo2O4 and CuCo2O4@CoMoO4-(1:1) prepared in Comparative Example 1 and Example 2 respectively are assembled into a half-cell (with lithium sheet as the counter electrode), and the specific capacity is about 1043mAh / g and 1180mAh / g at a current of 0.3A / mg; the half-cell assembled by CuCo2O4@CoMoO4-(1:1) in Example 2 has good charge and discharge stability, and the lithium-ion battery is also very stable.
[0066] Depend on Figure 3 It can be seen that the CuCo2O4 and CuCo2O4@CoMoO4-(1:1) prepared in Comparative Example 1 and Example 2 respectively are assembled into a half-cell (with lithium sheet as the counter electrode), and the specific capacity is about 935Ah / g and 1105mAh / g at a current of 0.5A / mg; the half-cell assembled by CuCo2O4@CoMoO4-(1:1) in Example 2 has good charge and discharge stability, and the lithium-ion battery is also very stable.
[0067] Depend on Figure 3 It can be seen that the CuCo2O4 and CuCo2O4@CoMoO4-(1:1) prepared in Comparative Example 1 and Example 2 respectively are assembled into a half-cell (with lithium sheet as the counter electrode), and the specific capacity is about 775mAh / g and 951mAh / g at a current of 1A / mg; the half-cell assembled by CuCo2O4@CoMoO4-(1:1) in Example 2 has good charge and discharge stability, and the lithium-ion battery is also very stable.
[0068] Depend on Figure 3It can be seen that the CuCo2O4 and CuCo2O4@CoMoO4-(1:1) prepared in Comparative Example 1 and Example 2 respectively are assembled into a half-cell (with lithium sheet as the counter electrode), and the specific capacity is about 503mAh / g and 737mAh / g at a current of 2A / mg; the half-cell assembled by CuCo2O4@CoMoO4-(1:1) in Example 2 has good charge and discharge stability, and the lithium-ion battery is also very stable.
[0069] The above performance graphs show that the CR2016 button battery in Example 2 of the present application, which uses copper cobaltate composite cobalt molybdate nanomaterials as negative electrode active materials, a lithium sheet as a counter electrode, 1M LiF6 as a solute, and EC and DEC as organic solvents (volume ratio 1:1) as an electrolyte, has good electrochemical performance, good battery rate performance, high coulombic efficiency and a long cycle life.
[0070] The present invention obtains CuCo2O4@CoMoO4 material by in-situ compounding of metal oxide cobalt molybdate through a combination of solvent heat and calcination. Since copper cobaltate is compounded with cobalt molybdate, the composite nanomaterial has excellent electrochemical properties and significant morphological changes.
[0071] The negative electrode material containing the copper cobaltate composite cobalt molybdate nanomaterial can enhance the conductive connection between electrode particles, significantly improve the specific capacity of the lithium-ion battery, and exhibit excellent rate performance and better cycle stability as an electrode material.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a copper cobaltate composite cobalt molybdate nanomaterial, characterized in that: The steps include: Step 1, weighing a copper source and a cobalt source, dissolving them in a first solvent, stirring evenly, to obtain a solution A; weighing a molybdenum source and a cobalt source, dissolving them in a second solvent, stirring evenly, to obtain a solution B; mixing solution A and solution B to obtain a mixed solution; Step 2, subjecting the mixed solution to a solvothermal reaction to obtain a precipitate, and washing and drying the precipitate to obtain an intermediate substance; Step 3: calcining the intermediate material to obtain copper cobaltate composite cobalt molybdate nanomaterial.
2. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 1, characterized in that: Step 1 specifically includes the following steps: A copper source and a cobalt source are weighed, dissolved in an organic solvent, and stirred and mixed evenly under a magnetic stirrer to obtain a solution A; a molybdenum source and a cobalt source are weighed, dissolved in dilute nitric acid, and stirred and mixed evenly under a magnetic stirrer to obtain a solution B; then solution B is slowly poured into solution A, and stirring and ultrasonic treatment are continued to obtain a mixed solution.
3. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 1, characterized in that: In step 2, the temperature of the solvent thermal reaction is 140° C., and the time of the solvent thermal reaction is 10 h.
4. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 1, characterized in that: In step three, the calcination conditions are: calcination in air, calcination temperature is 550° C., and calcination time is 1-5 h.
5. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 1 or 2, characterized in that: In step 1, the molar ratio of copper atoms, cobalt atoms and molybdenum atoms in the copper source, cobalt source and molybdenum source is 2:(4.5-5.5):(0.5-1.5).
6. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 1 or 2, characterized in that: In step 1, the copper source is one or more of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, and copper chloride; the cobalt source is one or more of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt chloride, and cobalt tetroxide; and the molybdenum source is one or more of ammonium molybdate, sodium molybdate, and magnesium molybdate.
7. The method for preparing a copper cobaltate composite cobalt molybdate nanomaterial according to claim 2, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, ethanol and acetone.
8. A copper cobaltate composite cobalt molybdate nanomaterial, characterized in that: Copper cobaltate composite cobalt molybdate nanomaterial prepared by the method described in any one of claims 1 to 7.
9. A negative electrode sheet, characterized in that: The negative electrode sheet contains the copper cobaltate composite cobalt molybdate nanomaterial described in claim 8 or the copper cobaltate composite cobalt molybdate nanomaterial prepared by the method described in any one of claims 1 to 7.
10. A battery, characterized in that: The invention comprises the negative electrode sheet as claimed in claim 9, and also comprises a battery casing, a positive electrode sheet, a separator and an electrolyte.